The German Response to Austria's Annexation of Cracow in 1846 - Šedivý, Miroslav (Oxford University Press, 2022)
The annexation of the Free City of Cracow by Austria in November 1846 has been regarded by historians as one of the most important international events in the period before the outbreak of revolutions in 1848. The annihilation of an independent state has been seen as a flagrant violation of international law that led to a weakening of Europeans' faith in the justice of the post-Napoleonic order. Consequently, it is surprising that even as this evaluation has become rooted in historical scholarship, the public response to this affair has scarcely been analysed. The aim of this article is to reveal the impact of the annexation on the broad public in the German Confederation and the decline in people's trust in justice in international relations. Germans across various political camps primarily perceived the annexation of Cracow not from the perspective of political modernization but in terms of geopolitical security. Their concern was not just with the position of the individual German states in relation to Prussia, Austria, Britain, France and Russia or the position of the entire German Confederation in relation to France, Britain and Russia, but also with their position within the political-legal system of European politics. The ensuing debate on the necessity for external security against threats from other European powers and nations became the most important outcome of this affair in Germany, with an egoistic, power-oriented response to the annexation of Cracow paving the way for conflicts among the Germans, Poles and other nations in 1848.
Německá reakce na rakouskou anexi Krakova v roce 1846
Keywords: Austria; Cracow, annexation; Germany; 1846; Rakousko; Krakov; anexe; Německo; 1846